Dynamic DNA methylation changes in the maternal oxytocin gene locus (OXT) during pregnancy predict postpartum maternal intrusiveness. (May 2019) - Toepfer, Philipp; O'Donnell, Kieran J.; Entringer, Sonja; Garg, Elika; Heim, Christine M.; Lin, David T.S.; MacIsaac, Julia L.; Kobor, Michael S.; Meaney, Michael J.; Provençal, Nadine; Binder, Elisabeth B.; Wadhwa, Pathik D.; et al.
Highlights: Oxytocin gene ( OXT ) promoter DNA methylation is dynamically changing throughout pregnancy. Dynamic OXT promotor DNA methylation during pregnancy predicts maternal postnatal behavior (intrusiveness). OXT promoter DNA methylation may serve as a prenatal biomarker in the prediction of maternal postnatal behavior. Abstract: Maternal behavior (MB) is observable across mammals and represents an important feature of environmental variation during early postnatal development. Oxytocin (OT) plays a crucial role in MB. Even prior to childbirth, pregnancy induces epigenetic and other downstream changes in the maternal OT-system, likely mediated by the actions of steroid hormones. However, little is known about the nature and consequences of epigenetic modifications in the maternal OT-encoding gene ( OXT ) during pregnancy. Our study aims to investigate temporal dynamics of OXT promoter DNA methylation (DNAm) throughout pregnancy in predicting MB in humans. In 107 mother-child dyads, maternal OXT DNAm was serially analyzed in whole blood in early, mid and late pregnancy. MB was coded based on standardized mother-child interactions at six months postpartum. After controlling for cellular heterogeneity, race/ethnicity, age, and socioeconomic status, OXT -promoter DNAm exhibited a dynamic profile during pregnancy ( b  = 0.026, t =-3.37, p < .001), with decreases in DNAm from early to mid-pregnancy and no further change until late pregnancy. Moreover, dynamic DNAm trajectories of the OXT -promoter region predicted MB (intrusiveness) at six months postpartum ( b  = 0.006, t  = 2.0, p < 0.05), with 6% higher OXT DNAm in late pregnancy in intrusive compared to non-intrusive mothers. We here demonstrate that OXT promoter DNAm changes significantly throughout gestation in peripheral blood and that these changes are associated with variability in MB, providing a novel potential biomarker predicting postnatal MB.